Windows 8 MVVM Patterns Revealed covers both C# and JavaScript - Ghoda, Ashish. (Apress : Imprint: Apress, 2012)
The Model-View-View-Model (MVVM) pattern is held in high regard by many developers as an excellent way of creating sophisticated modern applications. It's clear seperation of presentation and business logic produces a clean implementation that promotes speed, scalability and code reuse in applications with a complex UI. These strengths have found it favor with WPF and Silverlight developers. It is now increasingly being employed for Windows 8 apps, a purpose to which it is ideally suited as this book will show. In this brief, information-rich, guide we will show you how MVVM works with both XAML (C#) and HTML5 (JavaScript) flavors of Windows 8. Beginning with a brief recap of MVVM concepts under .NET - to provide a common frame of reference - we will then delve into the details of how MVVM can best be implemented in Metro-style apps for Windows 8 and show a working application framework in each case.